Targeting Protein–Protein Interactions in the HIF System. (21st March 2016) - Wilkins, Sarah E.; Abboud, Martine I.; Hancock, Rebecca L.; Schofield, Christopher J.
Abstract: Animals respond to chronic hypoxia by increasing the levels of a transcription factor known as the hypoxia‐inducible factor (HIF). HIF upregulates multiple genes, the products of which work to ameliorate the effects of limited oxygen at cellular and systemic levels. Hypoxia sensing by the HIF system involves hydroxylase‐catalysed post‐translational modifications of the HIF α‐subunits, which 1) signal for degradation of HIF‐α and 2) limit binding of HIF to transcriptional coactivator proteins. Because the hypoxic response is relevant to multiple disease states, therapeutic manipulation of the HIF‐mediated response has considerable medicinal potential. In addition to modulation of catalysis by the HIF hydroxylases, the HIF system manifests other possibilities for therapeutic intervention involving protein–protein and protein–nucleic acid interactions. Recent advances in our understanding of the structural biology and biochemistry of the HIF system are facilitating medicinal chemistry efforts. Herein we give an overview of the HIF system, focusing on structural knowledge of protein–protein interactions and how this might be used to modulate the hypoxic response for therapeutic benefit. Abstract : Targeting a big player : Hypoxia‐inducible transcription factors (HIFs) regulate the cellular response to hypoxia by promoting the expression of hundreds of genes including many of medical interest. The modulation of HIF activity is therefore a current objective of medicinal chemistry. Biochemical and biophysical analyses have revealed detailed insight into the protein–protein and protein–nucleic acid interactions central to the HIF system. We review knowledge of the oligomeric interactions central to the HIF system and attempts to modulate them using small molecules.